Analysis of agarwood smoke chemical compounds using solvent trap, GC-FID and GC-M - Nurlaila, Ismail; Mastura, Ibrahim; Seema, Zareen; Mohd Hezri, Fazalul Rahiman; Saiful Nizam, Tajuddin; Mohd Nasir, Taib (UPM Press, 2017)
Agarwood or gaharu, due to its unique scent and quality is considered one of the most expensive wood in the world. This paper uses solvent trap, Gas Chromatography-Flame Ionization Detector (GC-FID) and Gas Chromatography-Mass Spectrometry (GC-MS) to establish agarwood quality, and is part of ongoing research. The result showed that monoterpenes hydrocarbon, sesquiterpenes hydrocarbon and oxygenated sesquiterpene contribute to agarwood smoke. Among many compounds extracted, 2-hydrdoxy-benzaldehyde, β-selinene and guaia-1(10),11-dien-15,2-olide were found dominant in monoterpenes hydrocarbon, sesquiterpenes hydrocarbon and oxygenated sesquiterpenes respectively. This finding pointed to the utility of solvent trap in extracting chemical compounds of agarwood smoke. This study is also useful for further research on establishing the grade of agarwood.